The effectivity of Garlic (Allium sativum L.) and Turmeric (Curcuma longa L.) in Tilapia (Oreochromis niloticus) infected by Edwardsiella tarda - Novi Susanti; Dini Oktaviani; Leni Apriani; Gustriana Gustriana (Universitas Muhammadiyah Malang, 2022)
The aim of this study is to determine the effectivity of Garlic (Allium sativum L.) dan Turmeric (Curcuma longa L.) in Tilapia (Oreochromis niloticus) infected by Edwardsiella tarda. We used sensitivity test with disc diffusion Kirby-Bauer method. The 24 hours purified E. tarda isolate, cultivated in Mueller Hinton Agar (MHA) by swabbing it using a sterile swab on the MHA surface, next put paper disc contain variants garlic concentrations and turmeric. Incubated MHA on the room temperature (30 oC) for at least 24 hours, inhibition zone diameter is measured to see the effectivity. Serial Tube Dilution method is used to determine the Minimum Inhibitory Concentration (MIC) value for garlic and turmeric. Used as medication base on the second stage were 1 × MIC2 × MIC4 × MIC and 8 × MIC. Statistical analysis used completely randomized design, with 6 treatment and 4 repetition which density 10 ind/aquarium each. The result showed that garlic and turmeric inhibited E.tarda effectively, the highest survival rate was 1 × MIC at 8000 ppm for garlic and 1 × MIC at 20 ppm for turmeric. However, MIC level cannot be used as reference to determine the dose of herbal treatment, we can determine the dose by using disc volume in resistance test.